Uninhabitable earth : a story of the future - David Wallace-Wells (Gurgaon Penguin Random House, 2019)
It is worse, much worse, than you think. The slowness of climate change is a fairy tale, perhaps as pernicious as the one that says it isnt happening at all, and if your anxiety about it is dominated by fears of sea?level rise, you are barely scratching the surface of what terrors are possible, even within the lifetime of a teenager today. Over the past decades, the term "Anthropocene" has climbed into the popular imagination ? a name given to the geologic era we live in now, one defined by human intervention in the life of the planet. But however sanguine you might be about the proposition that we have ravaged the natural world, which we surely have, it is another thing entirely to consider the possibility that we have only provoked it, engineering first in ignorance and then in denial a climate system that will now go to war with us for many centuries, perhaps until it destroys us. In the meantime, it will remake us, transforming every aspect of the way we live?the planet no longer nurturing a dream of abundance, but a living nightmare.
Keywords: Climatic changes-Social aspects; Global warming-Social aspects